Computational insight into a mechanistic overview of water exchange kinetics and thermodynamic stabilities of bis and tris-aquated complexes of lanthanides. Issue 3 (6th January 2023) - Keot, Niharika; Sarma, Manabendra
Abstract : A thorough investigation of Ln 3+ complexes with more than one inner-sphere water molecule is crucial for designing high relaxivity contrast agents (CAs) used in magnetic resonance imaging (MRI). Abstract : A thorough investigation of Ln 3+ complexes with more than one inner-sphere water molecule is crucial for designing high relaxivity contrast agents (CAs) used in magnetic resonance imaging (MRI). This study accomplished a comparative stability analysis of two hexadentate (H3 cbda and H3 dpaa) and two heptadentate (H4 peada and H3 tpaa) ligands with Ln 3+ ions. The higher stability of the hexadentate H3 cbda and heptadentate H4 peada ligands has been confirmed by the binding affinity and Gibbs free energy analysis in aqueous solution. In addition, energy decomposition analysis (EDA) reveals the higher binding affinity of the peada 4− ligand than the cbda 3− ligand towards Ln 3+ ions due to the higher charge density of the peada 4− ligand. Moreover, a mechanistic overview of water exchange kinetics has been carried out based on the strength of the metal–water bond. The strength of the metal–water bond follows the trend Gd–O47 (w) > Gd–O39 (w) > Gd–O36 (w) in the case of the tris-aquated [Gd(cbda)(H2 O)3 ] and Gd–O43 (w) > Gd–O40 (w) for the bis-aquated [Gd(peada)(H2 O)2 ] − complex, which was confirmed by bond length, electron density ( ρ ), and electron localization function (ELF) at the corresponding bond critical points. Our analysis also predicts that the activation energy barrier decreases with the decrease in bond strength; hence k ex increases. The 17 O and 1 H hyperfine coupling constant values of all the coordinated water molecules were different, calculated by using the second-order Douglas–Kroll–Hess (DKH2) approach. Furthermore, the ionic nature of the bonding in the metal–ligand (M–L) bond was confirmed by the Quantum Theory of Atoms-In-Molecules (QTAIM) and ELF along with energy decomposition analysis (EDA). We hope that the results can be used as a basis for the design of highly efficient Gd(iii )-based high relaxivity MRI contrast agents for medical applications.